Atlantic cod (Gadus morhua) MHC I localizes to endolysosomal compartments independently of cytosolic sorting signals - Bjørnestad, Synne Arstad; Solbakken, Monica Hongrø; Jakobsen, Kjetill S.; Jentoft, Sissel; Bakke, Oddmund; Progida, Cinzia (Frontiers in Cell and Developmental Biology, 2023)
Major histocompatibility complex (MHC) class I and II are crucial for the adaptive immune system because they are involved in peptide presentation to T-cells. Until recently, it was believed that MHC genes and their associated immune components had been conserved since their evolutionary emergence in jawed fish. However, sequencing of the Atlantic cod (Gadus morhua) genome revealed a loss of MHC class II genes, and an extreme expansion of MHC class I genes. These findings lead to the hypothesis that a loss of the MHC class II pathway coincided with a more versatile use of MHC class I, but so far there is no direct experimental evidence in support of this. To gain a deeper understanding of the function of the expanded MHC class I, we selected five MHC class I gene variants representing five of the six clades identified in previous studies and investigated their intracellular localization in human and Atlantic cod larval cells. Intriguingly, we uncovered that all selected MHC class I variants localize to endolysosomal compartments in Atlantic cod cells. Additionally, by introducing point mutations or deletions in the cytosolic tail, we found that hypothetical sorting signals in the MHC class I cytosolic tail do not influence MHC class I trafficking. Moreover, we demonstrated that in Atlantic cod, tapasin and MHC class I colocalize on endolysosomes suggesting that peptide-loading assistance and stabilization of MHC class I occurs outside the endoplasmic reticulum. Altogether, our results demonstrate that MHC class I from Atlantic cod is sorted to the endolysosomal system, which may indicate that it interacts with exogenous peptides for potential cross presentation.